Assessment of Global Right Ventricular Function on 64-MDCT compared with MRI - Plumhans, C.; Mühlenbruch, G.; Rapaee, A.; Sim, Kui-Hian; Seyfarth, M.T; Günther, R.W; Mahnken, A.H (American Journal of Roentgenology, 2008)
Cédric Plumhans1, Georg Mühlenbruch1, Annuar Rapaee2, Kui-Hian Sim2, Tobias Seyfarth3, Rolf W. Günther1 and Andreas H. Mahnken1